Unusual Behaviour of Perfluorinated Cobalt Phthalocyanine Compared to Unsubstituted Cobalt Phthalocyanine for the Electrocatalytic Oxidation of Hydrazine. Effect of the Surface Concentration of the Catalyst on a Graphite Surface - Paez-Collio, M; Paez-Collio, M; Zagal-Moya, J; Zagal-Moya, J (2013)
It was found that CoPc and 16(F)CoPc when adsorbed on a graphite electrode exhibited voltammograms in alkaline solution (0.2 M NaOH) that show the typical redox peaks attributable to the reversible Co(II)/(I) redox process. The peak potential for CoPc was independent of the surface concentration of the catalyst. In contrast, for 16(F)CoPc, the Co(II)/(I) redox process shifted to more negative potentials with increasing surface concentration of the catalyst. In a volcano correlation of log (i?)E (activity per active site) versus the Co(II)/(I) formal potential of the catalyst (using several CoN4 chelates), CoPc appeared in the ascending portion (the activity increased with the Co (II)/(I) redox potential), whereas 16(F)CoPc appeared in the region where the activity decreases with the redox potential. In a plot of log (i/?)E versus the Co(II)/(I) formal potential of 16(F)CoPc, the declining portion of the volcano was reproduced for one single complex. Thus, 16(F)CoPc at different surface concentrations behaved as Co complexes, having different redox potential in the declining portion of the volcano plot, when the activity is normalized to the surface concentration. This was not observed for CoPc. Copyright 2013 (CC) SCS.
Keywords: cobalt phthalocyanine; cobalt-hexadecafluoro-phthalocyanine; surface concentration-dependent redox potential; hydrazine oxidation; electrocatalysis